The Moderating Effect of Adoption of Systematic Risk Management Procedure on The Performance of Commercial Real Estate Entrepreneurial Investments in Kenya - Mbugua , K J; Otuya , R; Muhanji , S (African Journal of Education,Science and Technology (AJEST), 2021)
The objective of this study was to assess the moderating effect of adoption of a systematic risk management procedure on the performance of commercial real estate entrepreneurial investments in Kenya. With a sample size of 384 participants drawn from a target population of 9,320 real estate entrepreneurs, the study used a descriptive survey method with a quantitative approach. The study target population was made up of 95, 320, 884and 8,021 people obtained from Kenya Developers, Estate Agent Registration Board, SoftKenya directory and National Construction Authority respectively. The participants were chosen using a stratified random sampling technique, and online questionnaires were sent via email. The Statistical Package for Social Sciences (SPSS) version 20.0 was used to perform descriptive and inferential analyses on primary data. Although only a small percentage of respondents use systematic risk management procedures, the majority (71.3%) of entrepreneurs relies on judgment, intuition, and general real estate industry experience to manage their risks, the study found that risk management practices used by real estate entrepreneurs have a significant moderating effect on commercial real estate performance. The study recommends the government to enhance policy issues that will help in increased adoption of risk management procedure and increase knowledge on real estate entrepreneurial investments risks and management amongst real estate entrepreneurs. The policy framework should include as a prerequisite submission of a risk management plan and staff training in risk management in any commercial real estate entrepreneurial investment approval.